2017
DOI: 10.18533/rss.v2i4.99
|View full text |Cite
|
Sign up to set email alerts
|

Site Suitability Analysis for Solid Waste Landfill Site Location Using Geographic Information Systems and Remote Sensing: A Case Study of Banket Town Board, Zimbabwe

Abstract: The aim of this study was to map the optimal sites that were environmentally suitable for locating a dumpsite in the Zimbabwean town of Banket as well as investigating the suitability of the dumpsite being currently used by the Banket Town Board. Geographic Information Systems and remote sensing constituted the main quantitative techniques used in data collection. Digitizing, buffering and overlaying were used to map suitable sites for locating a dumpsite in Banket. Environmental parameters were extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 7 publications
2
15
1
Order By: Relevance
“…Such unique district guideline should take preference over those from the higher level. The results in this study concur with the existing literature that showed the superiority of GIS-based multicriteria approach for site selection [9,21,22]. This superiority of the approach is not limited to landfill siting alone but also for infrastructure such as electric vehicle charging stations [31], bike-share stations [11] and potential ecotourism sites [32].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Such unique district guideline should take preference over those from the higher level. The results in this study concur with the existing literature that showed the superiority of GIS-based multicriteria approach for site selection [9,21,22]. This superiority of the approach is not limited to landfill siting alone but also for infrastructure such as electric vehicle charging stations [31], bike-share stations [11] and potential ecotourism sites [32].…”
Section: Discussionsupporting
confidence: 89%
“…Another reason could be the generally poor planning and modelling or proactive attitudes towards addressing problems in the country. Studies on landfill siting in Ghana [2, 7] and elsewhere [9,21,22] have shown that the standards set in the governmental guideline are inadequate to achieve environmental and health quality or prevent the issue of nimby, nimn and banana syndrome. It is not surprising that this phenomenon is common and widespread in the country [23,24], especially against landfill siting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it could be stated that in order to decrease the impact of the waste in a short term, establishing proper disposal sites could help and initiate a transition to more technological solutions when the basic needs are met (Nnorom & Osibanjo, 2008). Several studies (Henry et al, 2006;Jerie & Zulu, 2017;Idowu et al, 2019) have been done in developing countries on how to construct simple solutions, but appropriate promotion is lacking. These studies also emphasize on preparation and management of disposal sites which is a key issue at the moment.…”
Section: Introductionmentioning
confidence: 99%